Study on coated–liquid–liquid trimetal composite casting hammer. (May 2014) - Rong, S. F.; Zhao, X. M.; Zhou, H. T.; Wang, J. F.; Yao, J.; Li, C. H.
Abstract : In order to solve the problems of the fracture of the hammer head and the poor wear resistant of hammer handle in working conditions, the coated liquid–liquid trimetallic composite casting hammer was proposed. The core handler needed to be coated by high impact toughness and high wear resistant liquid high carbon high chromium steel to improve wear resistant of hammer handle. Then liquid high chromium cast iron was poured when the surface of liquid high carbon high chromium steel formed into certain thickness solid. The experimental results show that the wear resistant of the high carbon high chromium is as 3·2 times as low alloy steel. The perfect metallurgical bonding interface under the liquid–solid volume ratio of 8∶1 can be achieved by liquid–solid casting at 1565°C after the preheating 300°C.